Copper-Catalyzed Sulfonylation of Cyclobutanone Oxime Esters with Sulfonyl Hydrazides - Dong, Bingbing; Lu, Jiansha; Bao, Honghao; Zhang, Yuanyuan; Liu, Yingguo; Leng, Yuting (Synthesis, 2021)
A copper-catalyzed radical cross-coupling of cyclobutanone oxime esters with sulfonyl hydrazides has been developed. The copper-based catalytic system proved crucial for cleavage of the C−C bond of cyclobutanone oximes and for selective C–S bond-formation involving persistent sulfonyl-metal radical intermediates. This protocol is distinguished by the low-cost catalytic system, which does not require ligand, base, or toxic cyanide salt, and by the use of readily accessible starting materials, as well as broad substrate scope, providing an efficient approach to various diversely substituted cyano-containing sulfones.
Keywords: sulfonylation; radical cross-coupling; cyclobutanone oxime esters; sulfonyl hydrazides catalysis